O EFEITO DA APLICAÇÃO DO MICROGEO NA COMPACTAÇÃO DO SOLO - FANAIA, Elianay da Cruz Henrique; SANTOS, Wesley Vieira; MARTINS, Jennifer Caroline Vilalba; NASCIMENTO, Maryanne Ramos; MENEZES, Roniedison da Silva; PANACHUKI, Eloi (ANAIS DO ENIC, 2024)
-